2014
DOI: 10.1088/0004-637x/795/2/146
|View full text |Cite
|
Sign up to set email alerts
|

Recoiling Supermassive Black Holes: A Search in the Nearby Universe

Abstract: The coalescence of a binary black hole can be accompanied by a large gravitational recoil due to anisotropic emission of gravitational waves. A recoiling supermassive black hole (SBH) can subsequently undergo long-lived oscillations in the potential well of its host galaxy, suggesting that offset SBHs may be common in the cores of massive ellipticals. We have analyzed HST archival images of 14 nearby core ellipticals, finding evidence for small ( 10 pc) displacements between the AGN (locating the SBH) and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 164 publications
4
67
1
Order By: Relevance
“…Because a large offset from this location might disfavor a DM interpretation, we verify that the centroid of the excess is sufficiently close. An offset between the centroid of the DM halo and Sgr A* as large as approximately 2 • is consistent with numerical DM simulations, with the largest offsets tending to correlate with flatter central profiles [35,36]. An offset in the centroid position was previously reported in [13,37], while other studies of the GC excess have found it to be consistent with Sgr A*.…”
Section: B Nfw Centroidsupporting
confidence: 85%
“…Because a large offset from this location might disfavor a DM interpretation, we verify that the centroid of the excess is sufficiently close. An offset between the centroid of the DM halo and Sgr A* as large as approximately 2 • is consistent with numerical DM simulations, with the largest offsets tending to correlate with flatter central profiles [35,36]. An offset in the centroid position was previously reported in [13,37], while other studies of the GC excess have found it to be consistent with Sgr A*.…”
Section: B Nfw Centroidsupporting
confidence: 85%
“…This could be especially relevant for recoils in dry merger remnants, where the BH may undergo longlived, small-amplitude oscillations in a core potential (Gualandris & Merritt 2008;Lena et al 2014). Regardless, our results suggest that if BH spins are not highly aligned, a population of spatiallyoffset recoiling AGN may be resolvable with seeing-limited observations.…”
Section: Detection and Confirmation Of Recoiling Agnmentioning
confidence: 79%
“…For four of these nucleated galaxies (i.e., except for NGC 4365 and NGC 5419), both inner and mid are lower than 0.20 and their central light excess is due to a point-source AGN (Dullo & Graham 2012, their Section 8). For NGC 5419, Lena et al (2014) noted that it has a double nucleus (see also Lauer et al 2005). They found that the galaxy photocenter is displaced by ∼7.5 pc and 62 pc (i.e., 0.15R b,N5419 ) from these nuclei.…”
Section: Assessment Of the Ellipticity Measurementsmentioning
confidence: 98%